1989
DOI: 10.1016/0304-3959(89)90087-0
|View full text |Cite
|
Sign up to set email alerts
|

Pain from renal/ureteral calculosis: evaluation of sensory thresholds in the lumbar area

Abstract: Patients with unilateral renal/ureteral calculosis who had suffered a few painful attacks were examined. In the pain-free period, muscular, subcutaneous and cutaneous sensory thresholds to electrical stimulation were measured in the lumbar region (metamer L1) on both sides: (1) pain thresholds were lower on the affected side with respect to both the contralateral side and control thresholds recorded in normal subjects; (2) the greatest decrease in threshold was in the muscle (even the sensation of sustained co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 9 publications
2
52
0
Order By: Relevance
“…Previous clinical studies [26,27] in patients with unilateral renal/ureteral colics due to calculosis of the upper urinary tract have shown that hyperalgesia develops in the parietal tissues (skin, subcutaneous tissue and muscle) in the zone of pain referral, which long outlasts the painful episodes and is accentuated by their repetition [26 Á28]. A notable degree of referred parietal hyperalgesia was still detected in the pain-free period (in patients with few previous painful attacks) [27] and also in the absence of any a new calculosis after extracorporeal shock-wave lithotripsy [26].…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical studies [26,27] in patients with unilateral renal/ureteral colics due to calculosis of the upper urinary tract have shown that hyperalgesia develops in the parietal tissues (skin, subcutaneous tissue and muscle) in the zone of pain referral, which long outlasts the painful episodes and is accentuated by their repetition [26 Á28]. A notable degree of referred parietal hyperalgesia was still detected in the pain-free period (in patients with few previous painful attacks) [27] and also in the absence of any a new calculosis after extracorporeal shock-wave lithotripsy [26].…”
Section: Discussionmentioning
confidence: 99%
“…The former, in particular, is at the origin of a number of maneuvers specifically designed to detect referred deep hyperalgesia from various organs. The so-called "Giordano's maneuver," in the Italian clinical literature, for instance, reveals deep muscle hypersensitivity in patients with algogenic pathologies of the urinary tract; a clean blow is dealt to the lumbar region (L1) with the ulnar edge of the hand, which provokes a vigorous painful reaction by the patient in the case of hyperalgesia [21]. Similarly, Murphy's sign reveals referred muscle hyperalgesia in painful pathologies of the gallbladder; firm digital pressure is applied at the level of the cystic point while the patient is invited to inspire deeply (a procedure which puts the rectus abdominis muscle under contraction) [37].…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…By using different electrodes for the skin (surface electrodes) and for the subcutis and muscle (needle electrodes isolated their whole length except at the tip) and gradually increasing the intensity of the current, typical sensations can be evoked in each tissue. These are: 1) pricking pain for the skin, 2) linearly radiating prickling pain for the subcutis, and 3) cramp-like pain for the muscle [18][19][20][21][22][23].…”
Section: Experimental Muscle Pain In Humansmentioning
confidence: 99%
“…The patients exhibited a painful reaction when the border of the allodynic area was reached. 15, 33,35 (2) For the subcutis-pincer palpation, folds of tissue in the painful area were grasped between thumb and index finger and squeezed; hyperalgesia was revealed if the patients complained of discomfort. 36 (3) For the muscle, digital pressure was exerted firmly all over the painful area.…”
Section: Clinical Maneuvers For Detection Of Hypersensitivitymentioning
confidence: 99%